Psychotherapies and psychological support for individuals facing psychological distress during the COVID-19 pandemic: A scoping review. - Mao Yagihashi; Atsushi Sakuma; Michio Murakami (PLoS ONE)
In this scoping review, we investigated the psychotherapies and psychological support provided during the coronavirus disease 2019 (COVID-19) pandemic to clarify its recipients and the methods employed, among other characteristics. We used Scopus and PubMed as the two search engines and employed the following search terms: "COVID*" AND ("psychotherap*" OR "psychological support*") AND "psychological distress*." The first search was conducted on October 18, 2022, by reviewing search engines and conducting a manual search. It yielded 154 articles, of which 18 finally met the eligibility criteria after the second round of screening. The distribution of the participants in the intervention studies included in this review was diverse, including the general population, patients with COVID-19, and patients who had recovered from COVID-19. The implementation of psychotherapy was not limited to more advanced countries in psychiatry, indicating the broader reach of these interventions. Psychotherapy includes various methods, including cognitive behavioral therapy, acceptance commitment therapy, mindfulness, supportive care, virtual reality therapy, and online educational content via apps. The rise of new technologies may have increased the replacement rate of human therapists. In addition, the use of remote interventions was more common than that of face-to-face interventions. It is necessary to monitor whether the technologies and methods used for the first time during the pandemic will continue to be used in the future. Therefore, further research is needed to compare the effectiveness of remote randomized controlled trials with conventional face-to-face randomized controlled trials. Finally, most of those providing psychotherapies and psychological support in the studies included in this review were not doctors or psychologists.